LEGAL IMPLICATIONS OF THE UNILATERAL WITHDRAWAL OF FIDUCIARY GUARANTEE OBJECTS BY THE CREDITOR WITHOUT FOLLOWING LEGAL PROCEDURES - Raihan Ainurridho Matondang; Eka N.A.M Sihombing (Inspiring Law Journal, 2026)
The phenomenon of unilateral withdrawal of fiduciary collateral by creditors without proper procedures has become a serious problem in consumer financing practices in Indonesia. Many debtors experience forced repossession of collateral, such as motor vehicles, by debt collectors, who often use unlawful methods. This study aims to analyze the legal procedures for withdrawal of fiduciary collateral according to Law Number 42 of 1999, the legal consequences for creditors who carry out unilateral withdrawals, and the legal remedies debtors can take in dealing with this situation.The research method used in this study is normative legal with a case study approach. This research analyzes applicable laws and regulations, relevant legal doctrine, and field practices related to the withdrawal of fiduciary collateral. Data was collected through literature review and interviews with relevant parties, such as debtors, creditors, and legal practitioners.The research results show that unilateral withdrawal of fiduciary collateral by creditors without following legal procedures constitutes a violation that can lead to various legal consequences. Based on the research results, the procedure for withdrawing fiduciary collateral must be carried out in accordance with the provisions stipulated in Law Number 42 of 1999, including registration at the Fiduciary Registration Office and the issuance of a fiduciary collateral certificate. If creditors violate these provisions, they may be subject to criminal and civil sanctions, including claims for compensation from the debtor. The legal consequence for creditors who unilaterally withdraw collateral is the loss of preferential rights over the fiduciary collateral. In this case, the creditor cannot execute the collateral object without going through a legal process. In addition, the act of unlawful withdrawal can potentially give rise to a civil lawsuit by the debtor, who is entitled to compensation for losses suffered due to the unauthorized withdrawal. Debtors have a number of legal remedies that can be taken if they experience an unauthorized withdrawal of fiduciary collateral objects. They can ask the financing company to show a valid fiduciary collateral certificate, and if they cannot show one, the debtor does not need to hand over the collateral object. Debtors can also report unlawful acts to authorities, such as the Financial Services Authority or the Ministry of Finance, to obtain better legal protection.